Batik Wastewater Treatment Using TiO2 Nanoparticles Coated on the Surface of Plastic Sheet. (2017) - Sutisna,; Wibowo, Edy; Rokhmat, Mamat; Rahman, Dui Yanto; Murniati, Riri; Khairurrijal,; Abdullah, Mikrajuddin
Abstract: Batik is one of Indonesian cultures in the form of patterned fabric. As the rest of the coloring process, batik industries produce wastewater that can pollute the aquatic environment. Besides dyes, batik wastewater also contains synthetic compounds that are hard degraded, such as heavy metals, suspended solids, or organic compounds. In this study, TiO2 coated plastic sheets have been used to degrade batik wastewater under solar exposure. A total of 8 pieces of catalyst sheets are added on 1000 ml of the waste, and managed to degrade 50.41% of the initial concentration during 5-days irradiation. In this study, several parameters of the water quality such as chemical oxygen demand (COD), biological oxygen demand (BOD), and total suspensed solids (TSS) of the wastewater were observed to be decreasing during photodegradation process. The catalyst sheet also is stable to be used repeatedly in wastewater treatment.